2021
DOI: 10.1177/02683555211002340
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound criteria for lipedema diagnosis

Abstract: Background Lipedema is characterized by the deposition of abnormal fat in the lower and upper limbs bilaterally. It is a disease with high prevalence and genetic characteristics. Non-specific and non-quantified increases in the thickness of the subcutaneous tissue have previously been demonstrated using magnetic resonance imaging and computed tomography. Objectives To evaluate the thickness of the dermis and subcutaneous tissue in predetermined areas as a distinguishing feature between individuals with and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 14 publications
0
35
0
1
Order By: Relevance
“…Pitting edema over her feet suggested associated lymphedema, and the bilateral edema also suggested that the right lymphangitis was not the only cause of lymph-edema ( Figure 7 ). EDCV-MMII revealed only small superficial varicosities, while pre-tibial skin and subcutaneous thickness of 57.27 mm left and 55.9 mm right confirmed lipedema [ 23 ]. Lymphoscintigraphy was not requested because of infection.…”
Section: Case Reportsmentioning
confidence: 99%
“…Pitting edema over her feet suggested associated lymphedema, and the bilateral edema also suggested that the right lymphangitis was not the only cause of lymph-edema ( Figure 7 ). EDCV-MMII revealed only small superficial varicosities, while pre-tibial skin and subcutaneous thickness of 57.27 mm left and 55.9 mm right confirmed lipedema [ 23 ]. Lymphoscintigraphy was not requested because of infection.…”
Section: Case Reportsmentioning
confidence: 99%
“…It predominantly occurs in women. 5 Imaging exams such as ultrasound, 10 magnetic resonance, 11 and computed tomography 12 can confirm the diagnosis. Recently, Amato et al 13 published methodology for individual screening for lipedema using a self-administered questionnaire that showed excellent diagnostic accuracy, 14 making it possible to estimate the prevalence of lipedema using Brazilian census data.…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor, We read with great interest the article by Amato et al 1 which was recently published in your journal. We agree with the authors that it is important to determine the cut-off values using a simple and reproducible method for the diagnosis of lower extremity lipedema.…”
mentioning
confidence: 99%
“…3 Second, the authors defined the measured thickness for lipedema from dermis to the point where the subcutaneous tissue transforms into the fascia. 1 Herein, it is noteworthy that the etiopathogenesis of lipedema is still unclear and there are various hypotheses on the issue. 4 Because dermo-epidermal complex changes in lipedema (e.g.…”
mentioning
confidence: 99%